Hubungan Burnout Perawat Dengan Penerapan Keselamatan Pasien Di Ruang Instalasi Gawat Darurat RSUD Manembo – Nembo Bitung - Irma M. Yahya; Silvia Dewi M. Riu (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Safety the patient is very play a role important in prevention and subtraction risk, error medical, and injury physical, psychological, social, suffering, disability, or possible death happen during the service process health. Nurse sued for still give service the best that must be done make nurse prone to experience burnout. Goal study this for know connection nurse burnout with implementation safety patients in the Installation Room Emergency Manembo-Nembo Bitung Hospital Emergency. Research methods This use method Descriptive Analytic with design Cross sectional. Samples were taken based on amount population namely 40 respondents with use total sampling. Data collection was carried out use questionnaire. Furthermore, the data that has been collected processed use statistical test chi-square with level significance (α) ≤0.05. Research results show that nurse burnout part big in category high 25 respondents (62.5%) and implementation safety patient part big in category not enough good 22 respondents (55.0%), with statistical test results chi-square, namely p-value = 0.014, where p -value more small from value (α). Conclusions on the research There is connection nurse burnout with implementation safety patient in the room Installation Emergency Manembo Regional Hospital Emergency – Nembo Bitung. Expected nurse can implement and improve implementation safety patient in accordance with Standard Procedure Operational (SOP).